The Influence of Competence and Work Environment On Performance Mediated by Motivation Among Teachers At TK Mondial Batam - Manjorang, Marta Br; Ruspitasari, Widi Dewi (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: TK Mondial Batam is an international-standard kindergarten integrating national and international curricula through a trilingual approach while emphasizing character, creativity, and independence. Despite its strong reputation, the past three years show declining student enrollment and a shift in teacher performance from “very good” to “fair.” This study analyzes the influence of competence and the work environment on teacher performance, with motivation as a mediating variable. Background Problems: The study addresses declining enrollment and reduced teacher performance, leading to the question of how competence, work environment, and motivation affect teacher performance. Research Methods: A quantitative approach was used involving all 34 teachers through saturated sampling. Data were collected via an online questionnaire and analyzed using SMART PLS 4.0.6, incorporating validity, reliability, and model testing, supported by secondary data. Findings/Results: Results show that competence, work environment, and motivation each have positive and significant effects on teacher performance, and motivation significantly mediates the effects of competence and the work environment. Conclusion: The study concludes that improving competence, ensuring a supportive work environment, and strengthening motivation are essential to enhancing teacher performance and sustaining educational quality at TK Mondial Batam.sip